Analisis Faktor Produksi Industri Kerajinan Tenun di Kabupaten Jembrana - Pande Putu Gian Aryasuta; Made Dwi Setyadhi Mustika (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The development of the industrial sector is significantly influenced by various factors aimed at optimising resource utilisation. One notable product of small and medium enterprises (SMEs) in Bali is traditional handwoven fabric. This study aims to examine both the joint and individual effects of capital, working hours, raw materials, and business duration on the production level of the weaving craft industry in Jembrana Regency. A quantitative approach with an associative research method was employed. Data were collected from 94 weaving artisans, selected from a total population of 234 using the Proportionate Stratified Random Sampling technique. Data analysis included descriptive statistics, multiple linear regression, classical assumption tests, F-tests, and t-tests to assess the relationships among variables. The findings reveal that capital, working hours, raw materials, and business duration collectively have a significant effect on weaving production. However, partially, only capital and raw materials have a positive and significant impact, while working hours and business duration do not show significant effects. Therefore, weaving industry players in Jembrana are advised to better optimise the use of capital and raw materials in their production processes.